2002
DOI: 10.1002/pits.10010
|View full text |Cite
|
Sign up to set email alerts
|

Self‐report objective measures of personality for children: A review of psychometric properties for RQC

Abstract: Knoff (1995) indicated that Referral Question Consultation (RQC) can be applied to personality assessment and suggested several self‐report objective measures that could be consistent with this approach. The current article reviews the tools mentioned by Knoff, including the Children's Personality Questionnaire, The Millon Adolescent Clinical Inventory, The Minnesota Multiphasic Personality Inventory–Adolescents, The Personality Inventory for Youth, and The Self Report of Personality (SRP) from the Behavior As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For instance, commonly used measures like the Behavior Assessment System for Children or the Child Behavior Checklist (Achenbach, 1999), despite excellent psychometric properties, have been criticized as too lengthy, too expensive, and not sensitive enough to change to be administered on a continual or session-by-session basis (Burns, 2002;Drotar, Stein, & Perrin, 1995;Perrin, Stein, & Drotar, 1991).…”
mentioning
confidence: 99%
“…For instance, commonly used measures like the Behavior Assessment System for Children or the Child Behavior Checklist (Achenbach, 1999), despite excellent psychometric properties, have been criticized as too lengthy, too expensive, and not sensitive enough to change to be administered on a continual or session-by-session basis (Burns, 2002;Drotar, Stein, & Perrin, 1995;Perrin, Stein, & Drotar, 1991).…”
mentioning
confidence: 99%
“…On the BASC-2, for example, only the child self-report instrument measures self-perceptions and attitudes. And despite its lower reliability than the teacher report, the child self-report provides data on positive attributes, unlike most other self-report measures (Burns, 2002). Nonetheless, Grills and Ollendick (2003) have suggested that children younger than 10 may not have the ability to describe their feelings and behaviors accurately.…”
Section: Reconciling Results Across Multiple Informantsmentioning
confidence: 99%
“…However, interpretations of the existing studies that have included the MACI are severely limited due to issues with the structural validity and reliability of MACI scores. (Burns, 2002;Retzlaff, 1995).…”
Section: The Use Of Maci Scores For Discriminant Analysis and Concurrmentioning
confidence: 97%